Characterization of the complete plastid genome of Korean endemic, Ajuga spectabilis Nakai (Lamiaceae). Issue 1 (2nd January 2023) - Kamra, Kashish; Jung, Joonhyung; Kim, Hyuk-Jin; Yoon, Chang-Young; Kim, Joo-Hwan
Abstract: Ajuga spectabilis Nakai is a Korean endemic species in Lamiaceae. In spite of its importance, genomic studies are not performed on this species. Here, we report the complete plastid genome sequences of A. spectabilis, which will provide valuable information for its natural conservation and future studies for the plastid genome evolution. The plastid genome is 150, 417 bp in length, containing a large single-copy region (LSC) of 82, 140 bp and a small single-copy (SSC) region of 17, 165 bp which are separated by a pair of inverted repeats (IR) of 25, 556 bp. It encodes 113 genes, including 79 protein-coding genes, 30 tRNA genes, and four rRNA genes. The overall GC content is 38.3%, and those in the LSC, SSC, and IR regions are 36.4%, 32.2%, and 43.3%, respectively, which is consistent with other Ajuga species. Our phylogenetic analysis revealed that A. spectabilis formed a close relationship with A. ciliata and A. decumbens .